Divide, Conquer, and Sense: CD8+CD28− T Cells in Perspective - Arosa, Fernando A.; Esgalhado, André J.; Padrão, Carolina A.; Cardoso, Elsa M. (Frontiers in Immunology, 2017)
Understanding the rationale for the generation of a pool of highly differentiated effector-memory CD8+ T cells displaying a weakened capacity to scrutinize for peptides complexed with MHC class I molecules via their T cell receptor, lacking the “signal 2” CD28 receptor, and yet expressing a highly diverse array of innate receptors, from natural killer receptors (NKR), interleukin receptors and damage associated molecular pattern receptors, among others, is one of the most challenging issues in contemporary human immunology. The prevalence of these differentiated CD8+ cells, also known as CD8+CD28–, CD8+KIR+, NK-like CD8+ T cells, or innate CD8+ T cells, in non-lymphoid organs and tissues, in peripheral blood of healthy elderly, namely centenarians, but also in stressful and chronic inflammatory conditions suggests that they are not merely end-of-the-line dysfunctional cells. These experienced CD8+ T cells are highly diverse and capable of sensing a variety of TCR-independent signals, which enables them to respond and fine-tune tissue homeostasis.